SYNTACTIC AND SEMANTIC FEATURES OF ENGLISH VERB ‘GET’ WITH REFERENCE TO THEIR VIETNAMESE EQUIVALENTS IN THE NOVEL ‘VANITY FAIR’ BY W.M.THACKERAY / Lê Bích Diệp; NHDKH Assoc.Prof.Dr Lê Văn Thanh - Lê, Bích Diệp
The purpose of this study is to investigate the syntactic and semantics features of English verb get with reference to Vietnamese equivalent in the novel “Vanity Fair” by W.M. Thackeray. The study is aimed at three point: (1) finding the syntactic and semantics features of the verb get with reference to Vietnamese equivalent in the novel “Vanity Fair” by W.M. Thackeray, (2) finding the similarities and differences between the verb get in English and their equivalent in Vietnamese and (3) providing some recommendation for the teaching and learning as well as translation of verb get into the target language.This study was designed as a descriptive research with the method of contrastive and componential analysis. According to the data analysis, the result of the study show that the verb get coincide in their general meaning. However, the verb get in Vietnamese seems to have much more meanings than that in English. In practice, the study not only supplies some implications to language teaching, learning as well as translating but also raises language users’ awareness of the differences between the verb get so that they can use them exactly and be successful in their real life communication in English.